Analisis Pengaruh Konsumsi Rumah Tangga Untuk Pendidikan dan Kesehatan Terhadap Kesejahteraan Penduduk Kabupaten Mimika - Sartika Andi Yusuf; Rulan L Manduapessy (Journal of Economics and Regional Science, 2023)
This study aims to determine the significance of the effect of household consumption expenditure for education and health on the welfare of the population of Mimika Regency as proxied from the Mimika Regency Human Development Index. The data used in this study is secondary data obtained from BPS Mimika Regency through documentation techniques. To analyze the data used simple linear regression analysis. The results showed that household consumption expenditure for education and health had a significant effect on the welfare of the population of Mimika Regency as proxied from the Mimika Regency Human Development Index